Gram quantities of silver and alloy nanoparticles: synthesis through digestive ripening and the solvated metal atom dispersion (SMAD) method: antimicrobial properties, superlatteic[i.e. super lattice] selfassembly, and optical properties - Smetana, Alexander B. (Kansas State University, 2006)
This is an account of the synthesis of several drastically different forms of silver nanoparticles: Bare metal nanoparticles, dry nanoparticulate powders, aqueous soluble particles, and organic ligand coated monodisperse silver nanoparticles were all produced. The synthetic method was adapted from previous studies on gold nanoparticles and investigated to understand the optimal conditions for silver nanoparticle synthesis. Also the procedure for refinement of the nanoparticles was studied and applied to the formation of alloy nanoparticles. This extraordinary procedure produces beautifully colored colloids of spherical metal nanoparticles of the highest quality which under suitable conditions self-assemble into extensive three dimensional superlattice structures. The silver nanoparticle products were later tested against several biological pathogens to find dramatic increases in antimicrobial potency in comparison to commercially available silver preparations.
Keywords: Self-assembly; Silver nanoparticles; Superlattice 3-D; Antimicrobial properties; Alloy formation Au/Ag; Optical properties; Physics, Condensed Matter (0611)